TÜRKİYE’DE YOLSUZLUĞU ÖNLEMEYE YÖNELİK ÇALIŞMALARIN ETKİNLİĞİ - Alturki, Yousef Hasan Ali (TURAN : stratejik arastirmalar merkezi, 2025)
While this study focuses on corruption in depth, it specifically analyzes corruption in Turkey. The various definitions and scopes of corruption are examined, and Turkey's anti-corruption stance is examined based on international corruption indices. When analyzing regulations aimed at preventing corruption in Turkey, legal regulations and institutional structures are discussed. Furthermore, the effectiveness of these practices and institutional structures is investigated. When examining the existence of effective anti-corruption policies in Turkey, the contributions of regulations and institutional mechanisms that have emerged during this period are emphasized. Finally, in light of international comparisons, Turkey's current anti-corruption status and the need to strengthen the relevant framework are presented.